Lifestyle, health status and anxiety in students of University of Huelva - Concha Martínez-García; Ana Merchán-Clavellino; Yolanda Medina-Mesa; Rocío Guil (INFAD, 2018)
The WHO reports, concerning the health of young people aged from 20 to 24, highlight numerous health risk factors that increase the burden of morbidity, representing this current cohort of young people the largest that has ever existed in the world. Among these factors are included psychopathological disorders such as anxiety and depression, dietary alterations, alcohol and other illicit drugs consumption, and behavioral risk habits. This study aims to describe some aspects of lifestyle, self-perceived health status, and anxiety in a sample of healthy young students from the University of Huelva. The instruments used were a semi-structured interview on lifestyle and health status CRD (Martínez-García, et al., 2014) and ISRA (Miguel-Tobal Cano-Vindel, 2002). Participants were 102 university students (80.4% women), with an average age of 21.71 years (SD = 4.167). The results showed that participants had, in general terms, average socioeconomic level (82.4%) and healthy lifestyle in the family context. However, concerning their health status, it is noted that 14.9% of the sample admited “to drink more alcohol than they would like”, of which 73.4%, stated a consumption between 2 and 3 drinks and the remaining up to 7 drinks. The 11.8% of the sample showed illicit drugs consumptionand thesame proportion those who lost 10% of their weight in the last six months. The ISRA results showed diagnostic scores of severe Anxiety in 42.6% of the sample, 21.8% with marked anxiety, and 9.9% with extreme anxiety, correlating with alcohol variable the factors of the Total ISRA (Tb = -. 205; p = .017), Evaluation (Tb = -.219; p = .011) and Daily Life (Tb = -.228; p = .007). As a conclusion, we manifest the need to activate prevention protocols indicated by the WHO on these factors, in the university environment.